The Effects of Centella asiatica Leaves Gel Extract in Accelerating Healing Time of Shallow Grade II Burn at the White Rat (Rattus Norvegitus strain Wistar). - I Kadek Artawan (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Burn is skin tissue damage because of skin contact with a heat source such as fire, hot water, chemicals, electricity and radiation. Generally, burns wound care using conventional methods using normal saline (NaCl) 0,9% to various grades of wound, and some time that added with tulle grass inpragmanted paraffin. This method has many adverse effect, there are bleeding and painful during changing dressing. Therefore, current has been developed modern dressing using moist environment concept. One of them using gel formation. The aims of research was determine effects of centella asiatica Leaves gel extract in accelerating time of grade II burn healing at the white rats (Rattus Norvegitus strain Wistar). This research using true experimental design exactly Posttest Only Group Design. There are 18 samples that selected by simple random sampling, it is divided into two groups, there are treatment and control groups. Data collection using open eyes and wound care observation chart and then the data using independent sample t-test. The research results the mean healing time in treatment group 12,78 days and control group showed 15,67 days. The statistic value (Sig. (2-tailed)) is 0.002 which is smaller than ? (0,05), that means Ha was accepted so a significant difference between healing wound time using centella asiatica leaf gel extract iand normal saline 0,9%.